2011
DOI: 10.1111/j.1467-7652.2011.00603.x
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Pm3b wheat lines show resistance to powdery mildew in the field

Abstract: SummaryPlant resistance (R) genes are highly effective in protecting plants against diseases, but pathogens can overcome such genes relatively easily by adaptation. Consequently, in many cases R genes do not confer durable resistance in agricultural environments. One possible strategy to make the use of R genes more sustainable depends on the modification of R genes followed by transformation. To test a possible transgenic use of R genes, we overexpressed in wheat the Pm3b resistance gene against powdery milde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
136
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(151 citation statements)
references
References 97 publications
(202 reference statements)
13
136
1
1
Order By: Relevance
“…Transformation of genes involved in defense can improve resistance against FHB (12). Transgenesis also improved resistance to take all (54), Wheat streak mosaic virus (98), Barley stripe mosaic virus (115), LR (59), YR (40), and PM (11). Successful cloning of some wheat rust resistance genes offers opportunities to utilize multiple genes on the same construct as cis-gene cassettes for enhancing resistance durability (93).…”
Section: Improving Disease Resistance Through Marker-assisted Selectimentioning
confidence: 98%
“…Transformation of genes involved in defense can improve resistance against FHB (12). Transgenesis also improved resistance to take all (54), Wheat streak mosaic virus (98), Barley stripe mosaic virus (115), LR (59), YR (40), and PM (11). Successful cloning of some wheat rust resistance genes offers opportunities to utilize multiple genes on the same construct as cis-gene cassettes for enhancing resistance durability (93).…”
Section: Improving Disease Resistance Through Marker-assisted Selectimentioning
confidence: 98%
“…Notably, the powdery mildew resistance receptor, i.e., the CNL Pm8 derived from rye (Secale cereale), can form self-association complexes with its ortholog Pm3 or with different allelic forms of Pm3 in wheat (Brunner et al, 2011;Stirnweis et al, 2014). Since phylogenetic analysis has shown that BPH14 is more closely related to Pm8 than to most other known plant disease resistance proteins, studies on Pm8 and its ortholog Pm3 may provide some insight into its behavior.…”
Section: The Oligomerization Of Bph14 Is Implicated In Plant Immunitymentioning
confidence: 99%
“…Selective breeding still plays a major role in the production of new varieties but the emergence of modern plant biotechnology has led to a more targeted approach to increasing crop yields. Traits of agricultural importance successfully introduced to plants using recombinant DNA technology include herbicide resistance (Comai et al 1985), drought resistance (Kumar et al 2014), pest resistance (Bates et al 2005), pathogen resistance (Brunner et al 2011;Horvath et al 2012;Jones et al 2014), abiotic stress resistance (Jaglo-Ottosen et al 1998), enhanced photosynthetic capacity (Ku et al 2001), im-proved nitrogen use efficiency (Yanagisawa et al 2004), and added nutritional value (Ye et al 2000). However, although plants hold a unique promise for bioproduction at the gigatonne scale, efforts in genetic engineering of plants are lagging compared with microbial systems (Antunes et al 2009(Antunes et al , 2011Liu et al 2011Liu et al , 2013Koschmann et al 2012;Wend et al 2013;Zurcher et al 2013;Fethe et al 2014;Mül-ler et al 2014).…”
mentioning
confidence: 99%